Aplikasi Klaim Asuransi Kendaraan Bermotor untuk Mempermudah Pelanggan dengan Memanfaatkan Geolocation Positioning Guna Merekomendasikan Bengkel Terdekat - Muhammad Mahdi; Eko Hari Rachmawanto; Adiyah Mahiruna; Dila Ananda Oktafiani; Wahyu Dwy Permana; Fazlur Rahman Hafidz; Ardika Alaudin Arsa (Lembaga Pengembangan Kinerja Dosen, 2025)
Mobile phones can be used to communicate with each other quickly, whenever and wherever. With the rise of smartphones, users began to switch to using the internet as a medium of communication. Apart from being a communication device, today`s smartphone also has features and facilities that can be utilized to facilitate the work, such as cameras, GPS, and various sensors. Looking at this, business people are eager to create mobile apps to expand their business dimensions and to ease and provide better services to their customer. No exception is a vehicle insurance service company that intends to create a mobile application to provide services to its customers whenever and wherever they are. The application must enable the customer to file an insurance claim. Customers can also track the progress of the stages of claim work. At the time of the claim submission process, the customer may choose a partner workshop to work on the claim process. Because this app is mobile, it should also have a feature to search partner workshop located near the customer's location. So with the creation of mobile smartphone-based applications allow users to make claims and monitor / track claim progress on anywhere in real-time. The workshop search feature will use geolocation positioning method using GPS device on the smartphone to get the customer`s current location and search for a partner workshop within a certain radius.